What Human Rights Are There—if Any—and Why? - Endicott, Timothy (Studies in Christian ethics, 2010)
Are there human rights to a good such as social welfare, which depends on circumstances, and on the needs of a putative right-holder? Is justice constituted by rights? Does it take belief in God to understand the grounds of human rights? The essay responds to Nicholas Wolterstorff’s answers to these questions.